Ontologiczne podstawy edukacji religijnej w chrześcijaństwie - Wysocki, Adam (Kultura-Społeczeństwo-Edukacja, 2015)
The article indicates ontological bases which are at the ground of the religious education in Christianity. The touched problem considers issues of Christian anthropology and concerns the category of the person. The definite concept of the man forejudges applied pedagogic manners, that is the way of the approach to the pupil. The characteristics of the person indicates that for purposes of efforts of the man is his salvation, that in Christianity is the achievement of Communion with God, therefore the Christian religious education in its message points soteriological goals and measures. However nowadays, pluralism and multiculturalism and conditions of the public school extort using such type of the religious education which on one hand will accomplish ontological premises of Christian anthropology and on the other hand requirements of the present day.